Alarming Increase of Ketoacidosis Prevalence at Type 1 Diabetes-Onset in Austria—Results From a Nationwide Registry - Nagl, Katrin; Waldhör, Thomas; Hofer, Sabine E.; Fritsch, Maria; Meraner, Dagmar; Prchla, Christine; Rami-Merhar, Birgit; Fröhlich-Reiterer, Elke (Frontiers in Pediatrics, 2022)
Objective: We analyzed the annual prevalence of onset-DKA (diabetic ketoacidosis) from 2012 to 2020 with a sub-analysis for lockdown-periods during the COVID-19 pandemic in 2020. Design: All newly diagnosed children with type 1 diabetes (T1D) aged <15 years are prospectively registered in the population-based Austrian Diabetes Incidence Study in Austria. Main outcome measures: The annual DKA prevalence was analyzed using Joinpoint regression. Definition of DKA: pH<7.3, mild DKA: pH 7.3-≤7.1, severe DKA: pH<7.1. DKA prevalence during the lockdown periods in 2020 and the corresponding periods in 2015-2019 were examined using Fisher’s exact test. Results: In the years 2012-2020 the mean prevalence for onset-DKA in Austria was 43.6% (95%CI (confidence interval): 41.6,45.7) and thus above the mean prevalence of previous decades (1989-2011) of 37,1 % (95%CI: 35.6,38.6). A particularly high prevalence was found among children <2 years of age (72.0% DKA, 32.8% severe DKA). No significant gender difference was found. Prevalence of severe DKA at T1D-onset increased significantly since 2015 (p=0.023). During the lockdown in 2020, 59.3% of children were diagnosed with DKA at T1D-onset, compared to 42.1% during the previous 5 years (p=0.022). Moreover, 20% of children had severe DKA at T1D diagnosis, compared to 14% during the comparison period. Conclusions: The previously already high prevalence of DKA at T1D-onset has further increased over time. The COVID-19 pandemic has exacerbated the problem of a late or delayed diagnosis of diabetes in children resulting in onset-DKA. The alarmingly increased prevalence of DKA in Austrian children with T1D calls for urgent action.